TANGGUNG JAWAB PERUSAHAAN ATAS PEKERJA ALIH DAYA DALAM UNDANGUNDANG CIPTA KERJA : Studi Jaminan Kesejahteraan Berdasarkan Prinsip-Prinsip PBB Atas Bisnis dan HAM - Rachmani Aprilia Sari (2021)
Many regulations overlap and the growth of the percentage of unemployment in Indonesia, the Government tries to harmonize and harmonize these rules using the Omnibus Law system. Omnibus Law as a regulatory reform strategy, so that the arrangement is carried out simultaneously against many laws and regulations. Historically, omnibus law has previously been implemented in countries with common law system. One of the government's goals is to attract investors in Indonesia, thus opening up many jobs for the community. One of the 11 clusters of The Copyright Act, the most reaped the pros and cons is the Employment Cluster. Researchers are interested in one of the articles in the Copyright Act related to outsourced workers. Human rights and business are related to each other, it is stated in the Principles of Business Guidelines and Human Rights. The purpose of this research is how the company's liability to workers based on the Copyright Act and corporate liability is attributed to the United Nations Principles on Business and Human Rights. The method used in juridical research is normative. Normative juridical uses secondary data consisting of primary, secondary and tertiary legal materials. The result of the research is the responsibility of the company in the derivatives of the Copyright Act plays a full role in ensuring the welfare of workers until if a dispute between the two parties. The relationship between Business and Human Rights is interrelated because countries and companies have their respective roles in protecting, respecting and providing solutions contained in the implementation of UN principles. Indonesia has also ratified the 4 main points of the ILO Convention into national law regarding workers' rights, such as the Right to Freedom of Association and Organization, the Elimination of All Forms of Coercion in Work, the Elimination of Workers for Children, the Elimination of Discrimination in Terms of Employment and Positions.